The multiple combination of Paclitaxel, Ramucirumab and Elacridar reverses the paclitaxel-mediated resistance in gastric cancer cell lines - Schirizzi, Annalisa; Contino, Marialessandra; Carrieri, Livianna; Riganti, Chiara; De Leonardis, Giampiero; Scavo, Maria Principia; Perrone, Maria Grazia; Miciaccia, Morena; Kopecka, Joanna; Refolo, Maria Grazia; Lotesoriere, Claudio; Depalo, Nicoletta; et al. (Frontiers in Oncology, 2023)
Paclitaxel (PTX) interferes with microtubule architecture by binding to β-tubulin, thereby blocking progression at the G2/M phase and inducing apoptosis. This study aimed to investigate molecular processes underlying PTX-mediated resistance in gastric cancer (GC) cells. PTX-mediated resistance involves many processes, and in this work some of the factors involved in the resistance mechanism were identified by comparing two GC lines with PTX induced resistance to their sensitive counterparts. Thus, the key feature of PTX-resistant cells was the overexpression of pro-angiogenic factors such as VEGFA, VEGFC, and Ang2, known to support tumor cell growth. A second relevant change detected in PTX-resistant lines was the elevated level of TUBβIII, a tubulin isoform that opposes microtubule stabilization. A third identified factor contributing to PTX-resistance was P-glycoprotein (P-gp), a transporter responsible for chemotherapy efflux from the cells, highly expressed in PTX-resistant lines. These findings were in line with a greater sensitivity of resistant cells to treatment with both Ramucirumab and Elacridar. Ramucirumab significantly reduced the expression of angiogenic molecules and TUBβIII, while Elacridar restored the access of chemotherapy, recovering its anti-mitotic and pro-apoptotic effects. Finally, this study highlighted the role played by exosomes in spreading factors responsible for resistance in the tumor microenvironment.